Visual Landscape Study with the Visual Resources Assessment Procedure Method at Pekanbaru City Government Offices - Ramadhyna Prameswari Asyva; Qurrotu 'Aini Besila; Rini Fitri; Titiek Debora (Universitas Trisakti, 2022)
Pekanbaru City Government Office is a central office area as the city's central image that accommodates all government facilities, facilities, and infrastructure. This area has natural and artificial potential for design development in the area. The situation in terms of the landscape in this area is the lack of assessment and utilization of the visual aesthetic potential of the landscape in the Pekanbaru City Government Office area. The purpose of this study is to determine the visual aesthetic potential of the site by utilizing and optimizing natural and artificial visuals. This study uses a modified Visual Resources Assessment Procedure (VRAP). The results showed that the increase in the visual aesthetic value of the Pekanbaru City Government Office landscape design by examining the visual aesthetic aspects of the landscape as the basis for developing landscape design.